Impact of COVID-19 pandemic in the activity of a Therapeutic Apheresis unit in Italy. (December 2020) - Colpo, A.; Astolfi, L.; Tison, T.; De Silvestro, G.; Marson, P.
Abstract: Introduction: The recent Coronavirus Disease 2019 (COVID-19) outbreak has led to profound and rapid changes in the Italian and Veneto Region Healthcare System. This context also includes the quick reorganization which the Apheresis Unit (AU) of the Padova University Hospital, i.e. the Regional Reference Center for Therapeutic Apheresis (TA), had to face. Material and Methods: The study retrospectively evaluated the TA activity (procedures performed, patients treated and consultations) during the COVID-19 pandemic, from March to April 2020, comparing the activity in the same time period in 2018 and 2019. Results: In the period analyzed, a significant reduction in both the total number of procedures performed and of patients treated, respectively by 17 % and 16 % for the procedures and by 19 % and 20 % for patients treated compared to the same period of 2018 and 2019, respectively, was observed. A concomitant reduction in requests for TA consultation for new patients (both outpatients and inpatients) was observed, equal to 32 % and 21 % compared to 2018 and 2019, respectively. Conclusion: Many reasons determined the observed reduction in the TA activity during the recent COVID-19 outbreak. The AU itself was quickly reorganized in terms of location and supplies to allow for the appropriate COVID-19 patients care. Many non urgent cases, after multidisciplinary discussion between Clinicians and Apheresis Specialists, were deferred, maintaining close phone and e-mail contact with patients.